Når en trekant ikke bare er en trekant. Matematik og litteratur i det lange 1800-tal - Sørensen, Henrik Kragh (Passage - Tidsskrift for litteratur og kritik, 2018)
Henrik Kragh Sørensen: “When a Triangle is More than a Triangle. Mathema-tics and Literature in the Long 19th Century” Mathematical concepts such as triangles are very precisely defined in their geometrical context. Yet, these concepts gain new life outside the strict mathematical use. And outside of mathematics, triangles can have all kinds of symbolic meanings. In this article, three dimensions of the reference to mathematics in literature are discussed as it was manifested during the long 19th century. Mathematics contributed content, image and form to literary culture, and in particular to poetry. Thus, the strange mathematical universe and its language could be exploited, for instance for satirical ends. The three dimensions are illustrated through analyses of two poems from 1790s, namely Thomas Campbell’s “Pons Asinorum” and the parody “Loves of the Triangles” ascribed to a Mr Higgins.